Implementasi Customer Relationship Management (CRM) Pada Pendidikan Kursus Membaca Usia Dini - Rahmat Nugraha; Agun Guntara; Kiki Alibasah (Infoman's : Jurnal Ilmu-ilmu Informatika dan Manajemen, 2025)
The development of non-formal education institutions, particularly early childhood reading courses, requires effective management of relationships between institutions and customers, namely parents of students. Customer Relationship Management (CRM) is a strategic approach focused on managing long-term relationships with customers through the use of information technology. This study aims to analyze and examine the implementation of CRM in early childhood reading course institutions to improve service quality, customer satisfaction, and parent loyalty. The research method used is qualitative with a literature review and conceptual study approach based on various relevant scientific sources. The results indicate that CRM implementation in early childhood reading education can be carried out through three main stages: operational CRM, analytical CRM, and collaborative CRM. Integrated CRM implementation helps course institutions manage student data, enhance communication with parents, and support data-driven decision making. This study concludes that CRM plays an important role in improving competitiveness and sustainability of early childhood reading course institutions.